Marketing Strategy and Performance in Tourism Industry: SMART Tourism Development in Madura Island - SYARIF, Muh. (Journal of Environmental Management and Tourism, 2022)
This study aims to determine the growth factors, strategies, and performance of SMART. SMART stands for Specific, Measurable, Achievable, Relevant, and Time-Bound in the form of an effective process for determining and achieving business goals. The research design is a mix of methods to collect, process, and analyze data systematically and directly so that research can be carried out properly. Our findings reveal that the actual condition of the recovery of tourism industry, especially in Bangkalan, Sumenep, and Pamekasan regencies is getting better. The main challenge for the post-pandemic tourism industry is to promote local tourism on the international stage. It can be concluded that the SMART tourism framework can provide opportunities for businesses to determine their goals in facing the challenges of the tourism industry. Also, these findings reveal a lack of critical literature examining the assumptions of smart tourism and questioning its feasibility and positive experiential, economic and social impacts on local communities. This study proposes a research agenda that is far from comprehensive by understanding SMART's tourism potential and possible shortcomings and becomes a recommendation for government policies in the context of restoring the tourism industry in Indonesia.